Training zones in competitive swimming: a biophysical approach - Fernandes, Ricardo J.; Carvalho, Diogo D.; Figueiredo, Pedro (Frontiers in Sports and Active Living, 2024)
Since swimming performance depends on both physical conditioning and technical proficiency, training zones should be built based on physiology and biomechanics inputs to dispose of structured and effective training programs. This paper presents a zone-based swimming training, supported by the oxygen uptake (V˙O2) kinetics at low, moderate, heavy, severe and extreme intensities concurrently with lactate and heart rate values. Since technique is vital for efficiently moving through the water, upper limbs frequency and length should also be targeted during the workouts. The index of coordination was also added to our proposal since upper limbs synchronization is a key technical factor. To better establish and characterize a wide range of swimming intensities, the training methods and corresponding contents that better fit each training zone will be suggested. It will be shown that when under/at the anaerobic threshold (at low-to-moderate intensities), swimmers are at homeostasis and can maintain stable internal and external load indicators. However, above that boundary (at heavy and severe intensities), the physiological stable state is no longer observed and the anaerobic metabolism starts contributing significantly, with a technical degradation being more evident when performing near/at the V˙O2max intensity. Then, when performing above aerobic power, on typical anaerobic intensities, V˙O2 kinetics presents a very evident fast rise, ending abruptly due to exhaustion caused by muscle acidosis. This overall knowledge allows advancing toward more objective training programs and highlights the importance of systematic training control and swimmers' evaluation and advice.